Neintervencijsko spremljanje učinkovitosti in varnosti olanzapina (Zolrix) v zdravljenju shizofrenije in bipolarne manije - Bon, Jurij (Medicinski razgledi, 2011)
Schizophrenia and bipolar disorder are mental disorders that pose a real problem to the public health care system. Early diagnosis and treatment is instrumental in a relatively good management and control of these two diseeses. Second-generation antipsychotics increase the likelihood of selecting the right, optimal medicine, which enablcs effeceive treatment at reduced strength and frequency of adverse reactions. We conducted a post authorisation study in which 163 patients with schizophrenia and bipolar maniareceived olanzapine in the form of regular and orodispersible tablets (Zolrix / Zolrix orodispersible tablets, Krka, d. d., Novo mesto). Treatment with an average dose of 12.7 mg of olanzapine reduccd symptom expression in 79% of patients. Dueto improvement in symptoms 41%, of patients became only marginally ill or even symptom-free Olanzapine was very well tolerated by patients. Only in 25% of patients medicine-related adverse reactions were noted during monitoring, while at the end of monitoring the number feel to 17.8%. The post-authorisation study showed that the most frequent adverse reaction was weight gain, which was present in only 11% of patients treated with olanzapine.
Keywords: shizofrenija; therapy; zdravljenje; olanzapin; bipolarna manija; drug; zdravila